Validating the contributions of stem and root traits to barley lodging in western Canada - Taylor, Michael W.; Ferré, Céline A. M.; Ye, Shengjian; Yang, Xuan; Feurtado, J. Allan; Beattie, Aaron D. (Frontiers in Plant Science, 2025)
Lodging caused by stem buckling or root anchorage failure results in significant economic losses each year globally due to increased disease load, downgrading of quality, and yield loss. To increase lodging resistance in western Canadian barley, a study was undertaken to identify traits associated to lodging score. Mechanical and architectural traits encompassing whole plant, stem and root features of 13 spring barley genotypes, representing a diversity of classes, height, and lodging resistance, were evaluated at six field locations over three years. Correlation analysis identified plant height, internode length, crown root angle and root system solidity as traits with the largest influence on lodging (r = 0.37, 0.27, -0.32 and 0.62, respectively). A structural equation model (SEM) was created to further evaluate which traits had direct or indirect influence on barley lodging. The best fitting SEM included nine traits that captured aspects of the whole plant, stem and root system. Plant height (effect estimate = 0.46) and root system solidity (0.14) showed a direct influence on lodging, while root angle had both direct (-0.21) and indirect (via height) influence on lodging. Stem strength, stem outer diameter, and stem volume had indirect effects on lodging through height, while root network area, convex area and total root length had indirect effects on lodging through root system solidity. The three traits that directly influenced lodging in both correlation analysis and SEM, plant height, root angle, and root system solidity, displayed moderate to high heritability (0.85, 0.78 and 0.57, respectively), thus making them suitable for breeding selections. Collectively, this study confirmed the role of plant height and root angle in lodging, identified root system solidity as a novel trait associated to barley lodging resistance, and revealed root imaging as a new screening tool to help breeders select for, and improve, lodging resistance in the absence of observable field lodging.